Metagenomic and physicochemical profiling reveal microbial functions in pit mud for Jiang-Nong Jianxiang Baijiu fermentation - Lianbin Cao; Hongmei Sun; Ziyi Xu; Xiaoxiao Xu; Guangchuan Shi; Jianqiang Zhang; Changli Liang; Tongbiao Li; Chaoying Liu; Mingcheng Wang; Shilin Tian; Enzhong Li (BMC Microbiology)
Abstract Background The unique flavour and quality of Baijiu, a treasure of traditional Chinese culture, has attracted increasing attention. The pit mud is a key component for forming the unique flavour styles of different Baijiu brands. Hence, conducting in-depth research on the microbial colonies present in pit mud is paramount for enhancing the intricate bouquets of Baijiu flavours. Results This study conducts a comprehensive metagenomic examination of the microbial ecosystem within Chinese Jiang-Nong Jianxiang Baijiu fermentation pit mud. Within the pit mud walls, six prominent species, each accounting for more than 1% of the average relative abundance, emerged as key contributors: Lentilactobacillus buchneri, Secundilactobacillus silagincola, Clostridium tyrobutyricum, Lentilactobacillus parafarraginis, Ligilactobacillus acidipiscis, and Lactobacillus acetotolerans. Conversely, at the pit mud bases, four species surpassed this threshold: Petrimonas sp. IBARAKI, Methanosarcina barkeri, Methanofollis ethanolicus, and Proteiniphilum propionicum. Notably, the abundance of Clostridium in the pit mud walls impart superior saccharifying capabilities compared with those at the bases. The consistently high relative abundance of enzymes belonging to the glycoside hydrolases (GHs), glycosyltransferases (GTs), and carbohydrate-binding modules (CBMs) across both the pit mud walls and the bases highlight their importance in fermentation. Conclusions The microbial composition analysis results underscore the important role of pit mud microorganisms in facilitating starch saccharification, ethyl caproate and ethyl butyrate production, among other aromatic compounds. Microbes residing in the pit mud walls may be exhibited a heightened propensity for lactic acid generation, whereas those inhabiting the bases may be displayed a stronger inclination towards caproic acid production. This research serves as a valuable reference for future endeavours aimed at harnessing microbial resources to refine and optimize Baijiu fermentation methodologies.